Satan's Repentance: Carnivalesque in Asy-Syahiid Story By Taufiq Al-Chakim - Reza Sukma Nugraha (Arabic Literature Department, 2020)
Carnivalesque or carnival behavior is a concept coined by Mikhail Bakhtin about the suspension of all forms of social rules and hierarchies in literature. This is reflected in an Egyptian short story Asy-Syahiid written by Taufiq al-Chakim (1898-1987). The short story tells of a demonic character who wants to repent of his attitudes known as a human tempter. The satanic narrative described as contradicting the understanding of divine religion shows that al-Hakim tries to present the carnivalesque aspect in his work. This study will analyze the carnivalesque elements in the short story and the ideology behind the carnivalesque depictions. The method used is descriptive analysis method, namely by first describing the carnivalesque elements in the short story, then analyzing the ideology behind the depiction of these elements. The results showed that the short story Asy-Syahiid represented carnivalesque elements, such as profanation, comical elements, and multiplicity of tones. The ideology shown by the short story is a form of al-Hakim's criticism of humanity categorized by the devil's repentant narrative.